Analysis of the relation between glucose concentration in water and resonant frequency using the resonance model. (February 2020) - Akbar, M A; Rianto, S; Sakti, S P
Abstract: Any material specifically has an electric and magnetic property which can be expressed in term of its permeability and permittivity values. Liquid material has some electrical properties such as permeability and permittivity. In a certain configuration, the values are presented in a form of capacitance and inductance value. In this study, we developed a liquid impedance measurement system using RLC model to measure the existence of a glucose concentration in water. The RLC model can show the resonant frequency value of the analyte which is affected by the capacitance and inductance values. We found that the higher concentration gave higher resonance frequency. The parallel resonance frequency of the system is nonlinearly related to the glucose concentration. The series resonance frequency of the system increased by 22.4 kHz per 1% glucose concentration.